PRASI (KOMIK TRADISIONAL BALI) DI ERA DIGITAL, TANTANGAN DAN PELUANG - ida Bagus Rai (Universitas Pendidikan Ganesha, 2017)
Prasi (traditional Balinese comics) is one aspect of Balinese culture that supports the noble values and influences for the people of Bali. Prasi is a combination of two types of skills, namely the skills to write and draw on palm leaves. Prasi-shaped prose that accompanied the image using palm leaves as media. The types of stories written on prasi usually come from the epics of Ramayana and Bharatayudha. But there are also written from the story of Tantri. Prasi has function as entertainment media. The meaning contained in prasi is the values of religion and culture of Bali. The challenge of pration in the digital era, the community of the prasi is diminishing. The interest of the younger generation of Bali to write a few more prasi. Opportunities in the present era as a medium for preserving culture and religion in Bali. Prasi until now still favored by foreign tourists used as a cendramata